Optical re-injection in cavity-enhanced absorption spectroscopy - Leen, J. Brian (American Institute of Physics, 2014)
Non-mode-matched cavity-enhanced absorption spectrometry (e.g., cavity ringdown spectroscopy and integrated cavity output spectroscopy) is commonly used for the ultrasensitive detection of trace gases. These techniques are attractive for their simplicity and robustness, but their performance may be limited by the reflection of light from the front mirror and the resulting low optical transmission. Although this low transmitted power can sometimes be overcome with higher power lasers and lower noise detectors (e.g., in the near-infrared), many regimes exist where the available light intensity or photodetector sensitivity limits instrument performance (e.g., in the mid-infrared). In this article, we describe a method of repeatedly re-injecting light reflected off the front mirror of the optical cavity to boost the cavity's circulating power and deliver more light to the photodetector and thus increase the signal-to-noise ratio of the absorption measurement. We model and experimentally demonstrate the method's performance using off-axis cavity ringdown spectroscopy (OA-CRDS) with a broadly tunable external cavity quantum cascade laser. The power coupled through the cavity to the detector is increased by a factor of 22.5. The cavity loss is measured with a precision of 2 × 10(−10) cm(−1)/[Formula: see text] an increase of 12 times over the standard off-axis configuration without reinjection and comparable to the best reported sensitivities in the mid-infrared. Finally, the re-injected CRDS system is used to measure the spectrum of several volatile organic compounds, demonstrating the improved ability to resolve weakly absorbing spectroscopic features.